Relevansi Hukum dengan Undang-Undang No. 11 Tahun 2020 tentang Cipta Kerja Menggunakan Pendekatan Maslahat - Nunuk Parwati Songki; Said Syaripuddin; Ilyas Umar (Al-Tafaqquh: Journal of Islamic Law, 2023)
The main problem in this research is to examine issues regarding the concept of Law Number 11 of 2020 concerning Job Creation Using the Maslahat Approach, regarding the view of Islamic Law regarding Law No. 11 of 2020 concerning Job Creation, the benefits of Law no. 11 of 2020 concerning Job Creation for workers and the existence of Law no. 11 of 2020 concerning Job Creation from the perspective of Sharia Economic Law. The type of research used in this research is library research (Library Research). The data sources used are primary data and secondary data. The results of this study are that the review of Islamic law in Law no. 11 of 2020 concerning Job Creation is a form of maintaining the soul (hifzh al-nafs) in principle maqashid syari'ah as a means of defending their economic right to survive. As for the benefits of Law no. 11 of 2020 concerning Job Creation that can be felt for now, namely: creating jobs, encouraging investment, permitting systems that are easier and faster, and investment requirements made easier. The value of Sharia Economic Law in terms of Law no. 11 of 2020 concerning Job Creation, providing Islamic economic growth, especially to the Islamic finance industry in Indonesia such as Islamic Banks, Non-Bank Islamic Financial Industry, Islamic Cooperatives and Islamic Capital Markets, in the future there will be great opportunities in running their business.